Perspectives for Remote Sensing with Unmanned Aerial Vehicles in Precision Agriculture. (February 2019) - Maes, Wouter H.; Steppe, Kathy
Abstract : Remote sensing with unmanned aerial vehicles (UAVs) is a game-changer in precision agriculture. It offers unprecedented spectral, spatial, and temporal resolution, but can also provide detailed vegetation height data and multiangular observations. In this article, we review the progress of remote sensing with UAVs in drought stress, in weed and pathogen detection, in nutrient status and growth vigor assessment, and in yield prediction. To transfer this knowledge to everyday practice of precision agriculture, future research should focus on exploiting the complementarity of hyperspectral or multispectral data with thermal data, on integrating observations into robust transfer or growth models rather than linear regression models, and on combining UAV products with other spatially explicit information. Highlights: Drought stress detection with unmanned aerial vehicles (UAVs) relies mainly on thermal imagery. Pathogen detection with UAVs is relatively premature, but fusion of thermal and hyperspectral data shows great potential. Weed detection with UAVs based on object-based image analysis is in an advanced stage, and can be used for site-specific weed management. Nutrient status assessment and yield prediction with UAVs are promising, but integration with models can improve its applicability.